ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PELANGGAN DALAM MEMILIH JASA SERVICE KOMPUTER ITSHAN INFOTIKA DI KOTA TIMIKA - Faris Rodolfo Nes; Qur Annisa Nurul Pratiwi; Ahmad Tomu (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to determine the factors that influence customer decisions in choosing computer services from Itshan Infotika in Timika. The data collected in this study is qualitative data in the form of statements from customer decisions in the form of questionnaires. The data analysis in this study used multiple linear regression. From the results of the analysis that has been carried out, it was found that service quality, reputation and security are factors that influence customer decisions in choosing Itshan Infotika computer services in Timika city. Thus, the most influential and significant factors are reputation and security.